Angiographic, optical coherence tomography and histology findings from combination of a drug-coated balloon with an everolimus-eluting stent in a porcine model. (15th November 2016) - Ong, Paul J.L.; Kubo, Takashi; Watson, Timothy J.; Seah, Agnes S.P.; Wong, Philip E.H.; Akasaka, Takashi
Abstract: Background: We designed a porcine model to compare the angiographic, optical coherence tomography (OCT) and histological findings of implanting an everolimus-eluting stent (EES) in the same segment of the coronary artery pre-treated with a drug-coating balloon (DCB; paccocath as carrier) with EES alone and DCB plus a bare metal stent (BMS). Methods: Seven female swine averaging 46.0 ± 2.4 kg were treated by random assignment as follows: DCB followed by EES; DCB followed by BMS; and EES alone. Quantitative coronary angiography (QCA) and OCT were carried out post-implantation and repeated after 28 ± 1 days. Results: All arteries remained patent and demonstrated no sign of thrombus formation. There was no significant difference at 1 month between the treatment groups in lumen loss (0.64 ± 0.43, 0.44 ± 0.43 and 0.33 ± 0.28 mm for EES, DCB/EES and DCB/BMS respectively, p = 0.37) and binary restenosis (6.86 (2.91–9.12), 4.93 (− 1.53–10.7) and 4.18 (3.27–10.2)% respectively, p = 0.87). OCT found mean neointimal thickness of 0.15 ± 0.09, 0.07 ± 0.03 and 0.08 ± 0.03 mm (p = 0.05) for EES, DCB/EES and DCB/BMS respectively. Endothelial strut coverage was 92.3 ± 5.5, 85.4 ± 8.6 and 89.1 ± 8.9% (p = 0.05) and mean neointimal area was 1.06 ± 0.42, 0.95 ± 0.24 and 1.20 ± 0.28 mm 2 (p = 0.09) respectively. Inflammation score was similar between the three groups: 0.20 (0.20–0.28), 0.30 (0.22–0.48), 0.30 (0.20–0.38) for EES, DCB/EES and DCB/BMS respectively (p = 0.14) and there were no differences in fibrin deposition. Conclusions: The combination of DCB with EES appeared to be safe and effective. Using EES to bail out suboptimal DCB therapy appeared to be safe and effective in this porcine model.